2021
DOI: 10.3390/pathogens10020095
|View full text |Cite
|
Sign up to set email alerts
|

Towards New Horizons: Climate Trends in Europe Increase the Environmental Suitability for Permanent Populations of Hyalomma marginatum (Ixodidae)

Abstract: Ticks and tick-borne pathogens are changing their current distribution, presumably due to the impact of the climate trends. On a large scale, these trends are changing the environmental suitability of Hyalomma marginatum, the main vector of several pathogens affecting human health. We generated annual models of environmental suitability for the tick in the period 1970–2018, using harmonic regression-derived data of the daily maximum and minimum temperature, soil moisture and water vapor deficit. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…This relationship could be explained by the xerophilic nature of this tick with the assumed inability of non‐parasitic stages to survive in flooded areas, as egg mortality and development anomaly at high RH had been reported (Buczek, 2000 ; Morel, 2003 ). This confirms the findings of Fernández‐Ruiz and Estrada‐Peña ( 2021 ) who reported that a decrease in soil humidity within a Mediterranean‐type habitat was associated with an increase in environmental suitability for H. marginatum . Such humid habitats are commonly found in Camargue, which settles at the mouth of the Rhône River in Bouches‐du‐Rhône (13), where H. marginatum introductions are very likely through migratory birds (as shown by several single‐presence records) but where large plains remain humid all year long, favouring cattle and horse rearing but not tick establishment.…”
Section: Discussionsupporting
confidence: 91%
“…This relationship could be explained by the xerophilic nature of this tick with the assumed inability of non‐parasitic stages to survive in flooded areas, as egg mortality and development anomaly at high RH had been reported (Buczek, 2000 ; Morel, 2003 ). This confirms the findings of Fernández‐Ruiz and Estrada‐Peña ( 2021 ) who reported that a decrease in soil humidity within a Mediterranean‐type habitat was associated with an increase in environmental suitability for H. marginatum . Such humid habitats are commonly found in Camargue, which settles at the mouth of the Rhône River in Bouches‐du‐Rhône (13), where H. marginatum introductions are very likely through migratory birds (as shown by several single‐presence records) but where large plains remain humid all year long, favouring cattle and horse rearing but not tick establishment.…”
Section: Discussionsupporting
confidence: 91%
“…The area of CCHFV detection coincides with the region where the ecologic conditions are more favorable for the presence of H. marginatum and H. lusitanicum ticks, the main vectors of the disease. Neither of these species have been reported in northeastern Spain, but ecologic models predict the existence of areas suitable for H. marginatum (11). To evaluate possible CCHFV circulation in Catalonia, northeastern Spain, we conducted a serosurvey to detect CCHFV antibodies in different susceptible wild animal species.…”
mentioning
confidence: 99%
“…Firstly, the geographic information of H. marginatum was recorded on a separate data sheet. Secondly, these raw records were cleaned and reduced by removing localities, (1) where tick collection had been conducted from birds since finding ticks on birds does not mean that ticks can establish populations in these areas (Estrada-Peña et al, 2011;Fernández-Ruiz & Estrada-Peña, 2021); (2) sampling information from Cyprus was removed as molecular data does not confirm that H. marginatum exists in Cyprus (Hekimoglu & Ozer, 2017). After these steps, a total of 565 geographic coordinates were obtained.…”
Section: Occurrence Recordsmentioning
confidence: 99%
“…The Mediterranean region is among the areas projected to be most negatively affected by climate change (Bardsley & Edwards-Jones, 2007;Newbold et al, 2020;Ulbrich et al, 2006). Studies have indicated an increase in CCHF transmission in the Mediterranean basin (Maltezou & Papa, 2010) and a tendency for the northward expansion of CCHF's range in the Mediterranean (Andersen & Davis, 2017;Estrada-Peña & Venzal, 2007;Fernández-Ruiz & Estrada-Peña, 2021;Williams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%